STUDENTS’ EXPERIENCE IN BUILDING LITERACY THROUGH BOOKTALKS PROGRAM - Erna Irawati (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2019)
In this study, student ownership of devices actually became a phenomenon found in the field that they could use to find various books in many electronic book applications easily. In previous research, this has become one of the supporting factors of successful booktalks program implementation carried out by researchers. This study uses a qualitative method by exploring student perspectives on the application of booktalks program that utilizes gadget through the application of electronic books in building students’ literacy, the culture of reading and writing. 27 students participated in this study by submitting reflective notes that answered 2 questions about the advantages and challenges that students felt about implementing booktalks program that utilizes electronic book applications. Through content analysis, the results of data analysis showed students positive responses to the implementation of booktalks program that utilizes various electronic book applications in building student literacy.